Entrepreneurial intention: Creativity, entrepreneurship, and university support - Temoor Anjum; Muhammad Farrukh; Petra Heidler; Julián Andres Díaz Tautiva (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
To study the impact of perceived creativity disposition on entrepreneurial attitude and intentions, based on the theory of planned behavior, a model of the relationship between perceived creativity disposition and entrepreneurial intentions and attitude was constructed, relevant hypotheses were proposed, and the moderation mechanism of perception of university support on perceived creativity disposition and entrepreneurial intentions was also developed and analyzed. The study population included university business students in Pakistan. A sample of 330 students was selected from eight universities in Lahore and Islamabad, Pakistan. A random stratified sampling technique was executed. For this study, a cross-sectional and quantitative research design was used based on the survey process. The two-part questionnaire was used for data collection. Smart-PLS software version 3.2.7 was used to assess the hypothesis of this study. It was found that perceived creativity disposition and attitude toward entrepreneurship has a positive influence on entrepreneurial intention. It was also discovered that the perception of university support moderates the relationship between perceived creativity disposition and entrepreneurial intention. In this study, the moderation effect of perception of university support on the relationship between perceived creativity disposition and entrepreneurial intention was acknowledged. As a policy implication, the government should ensure students with an innovative entrepreneurial environment and well-built perception of university support are supported through different channels. Finally, a conceptual model was proposed based on adopting the theory of planned behavior, and the study ends with a conclusion and implications for future research.
Keywords: 650; attitude toward entrepreneurship; entrepreneurial intention; perceived creativity disposition; perception of university support; theory of planned behavior